Biological and anticancer properties of Inonotus obliquus extracts. (October 2018) - Szychowski, Konrad A.; Rybczyńska-Tkaczyk, Kamila; Tobiasz, Jakub; Yelnytska-Stawasz, Viktoriya; Pomianek, Tadeusz; Gmiński, Jan
Graphical abstract: Highlights: I. obliquus increased antioxidative enzymes expression in the fibroblasts cells. I. obliquus decreased enzymes expression in the colorectal adenocarcinoma cells. I. obliquus decreased reactive oxygen species production in the fibroblasts cells. I. obliquus increased reactive oxygen species production in the carcinoma cells. Abstract: Inonotus obliquus (IO) has traditionally been used in folk medicine in the treatment of gastrointestinal cancer, cardiovascular disease and diabetes. The aim of our study was to evaluate the biological and metabolic properties of IO extracts. Free radical scavenging properties, inhibition of the activity of xanthine oxidase (XOi), induction of reactive oxygen species (ROS) production, cell viability and expression of superoxide dismutase ( SOD1), catalase ( CAT) and KI67 mRNA in the human colorectal adenocarcinoma (Caco-2) and normal human skin fibroblast (BJ) cell lines were measured. It was found that 80% ethanol extract of IO exhibited the highest properties inhibiting the activity of XO and radical scavenging activities. PBS, ethanol and methanol extracts of IO increased ROS production in the Caco-2 cell line. Moreover, the ethanol extract of IO increased SOD1, CAT and KI67 mRNA expression and decreased ROS production in the BJ cell line. Alternately, PBS, ethanol and methanol extracts of IO decreased ROS production and SOD1, CAT and KI67 mRNA expression in Caco-2. The present study revealed, for the first time that IO extract acts in different way in normal and cancerous cell culture. Moreover cytotoxic mechanism of action can be partially ROS-dependent.